Effect of Weight Reduction Following Bariatric Surgery on Serum Visfatin and Adiponectin Levels in Morbidly Obese Subjects - Mohammad Javad Hosseinzadeh-Attar; Atefeh Golpaie; Leila Janani; Hoda Derakhshanian (Obesity Facts, 2013)
Objective: Adipokines are signaling and mediator proteins secreted from adipose tissue. A novel adipokine, visfatin, was reported as a protein which was mainly expressed in visceral adipose tissue. Controversial results have been shown regarding the changes of adipokines following weight reduction. So we investigated the effects of weight reduction on serum concentrations of adiponectin and visfatin in morbidly obese subjects. Methods: 35 severely obese patients (26 females and 9 males), aged 15-58 years, were studied. Anthropometric parameters and biochemical parameters as well as adiponectin and visfatin were analyzed before and 6 weeks after weight reduction. Results: Anthropometric indices decreased significantly. Blood levels of low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and triglyceride were reduced significantly. The reduction of visfatin and the elevation of adiponectin were significant as well. However, other parameters like fasting glucose and insulin did not change. Moreover, we could not find any significant correlation between the change of serum visfatin and that of adiponectin. Conclusions: 6-week weight reduction after bariatric surgery resulted in decreased serum visfatin and increased adiponectin levels. However, we cannot find any significant correlation between changes of adiponectin, visfatin, BMI, waist circumference, and insulin resistance. Further studies with different design are suggested to clarify these associations.